Viral codon usage and the virus-host interactions - Sirihongthong, Thanyaporn; Auewarakul, Prasert (Frontiers in Microbiology, 2025)
Codon usage pattern is a specific characteristic of each species as a result of evolution and interaction between genome composition and translational machinery. Species-specific optimal codon usage is a requirement for efficient expression in cells of that species. Viruses pose a curious situation where their genomes must interact with their hosts. Codon usage and genome composition of most viruses infecting eukaryotic hosts are markedly different from those of their hosts. How these viruses efficiently express their genes with non-optimal codon usage is not well understood. Some evidence suggests that they may manipulate host translational machinery to achieve this. On the other hand, host cells may launch innate antiviral defense to suppress expression of viral genes with non-optimal codon usage. Codon usages of viruses are more similar among viruses within the same genome type. This suggests that there may be common mechanisms driving codon usage of viruses within the same genome type. These interactions may contribute to host adaptation in inter-species transmission and viral emergence. However, direct adaptation to be more similar with host codon usage pattern is not always the case. Complex viral-host interaction may direct evolution of viral codon usage. More understanding in these interactions may provide new insight into the viral evolution and host adaptation and offer new possibilities in fighting against new and old viruses. Here we review various aspects of these interactions.